1998
DOI: 10.1164/ajrccm.158.1.9710101
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Particulate and Other Air Pollutants and Lung Function in Nonsmokers

Abstract: The associations between lung function measures (spirometry and peak expiratory flow lability) and estimated 20-yr ambient concentrations of respirable particles, suspended sulfates, sulfur dioxide, ozone, and indoor particles were studied in a sample of 1,391 nonsmokers followed since 1977. Differences in air pollutants across the population were associated with decrements of lung function. An increase of 54 d/yr when particles < 10 micro(m) in diameter (PM10) exceeded 100 microg/m3 was associated with a 7.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
4
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(127 citation statements)
references
References 31 publications
4
116
4
3
Order By: Relevance
“…Two other observational studies demonstrated a relation between ETS exposure and decreased forced expiratory flow, midexpiratory phase (FEF 25%-75% ), but not FEV 1 or FVC (35,36). Other investigators have found no consistent relationship between ETS exposure and pulmonary function in adults (37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 98%
“…Two other observational studies demonstrated a relation between ETS exposure and decreased forced expiratory flow, midexpiratory phase (FEF 25%-75% ), but not FEV 1 or FVC (35,36). Other investigators have found no consistent relationship between ETS exposure and pulmonary function in adults (37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 98%
“…The risk of asthma onset or chronic effects on asthma from ambient air pollution exposure has been less clearly identified in epidemiologic studies, although few studies are prospective cohort designs (6)(7)(8)(9)(10)(11)(12)(13). A cohort study of nonsmoking adult Seventh Day Adventists in California followed 10 or more years found associations between the development of asthma and outdoor concentrations of total suspended particulates (11), total suspended sulfate (12), and ozone (O 3 ) (13).…”
Section: Importancementioning
confidence: 99%
“…Time series studies (Pope et al, 1992;Schwartz, 1994aSchwartz, ,b, 1997Schwartz, , 1999Schwartz and Dockery, 1992;BorjaAburto et al, 1998 ) of acute impacts have been complemented by evidence from prospective cohort studies ( Dockery et al, 1993;Pope et al, 1995a,b;Abbey et al, 1998 ). To support these epidemiological associations, much current research is focused on the elucidation of biologically plausible mechanisms through which airborne particles may act ( NRC, 1998 ) .…”
Section: Introductionmentioning
confidence: 99%